Study of spatial layout and its effect on privacy provision in Malaysian contemporary housing - Abdul Rahim, Asiah (s.n, 2012)
Housing design has significantly changing due to the mass production of housing, modernization, technological advancement with different human thoughts and a diverse housing preference and needs. This eventually has contributed to the new interpretation and definition of privacy among human, not excluding the Muslims, which apparently created a non-satisfaction, uncomfortable feeling and the sense of otherness to its users, especially the Muslim man and woman who practice the Islamic teachings. This on-going research proposes to investigate the space analysis of typical contemporary housing layout designs and its effects on the level of privacy provided. This research, to some extent attempts to reveal few lessons from the Malay traditional house for designing contemporary house with suitable level of privacy to fulfil the complex needs of human, especially with regards to Muslim woman’s privacy in the house. The methodology applied will be based on table research. This study attempts to suggest design strategies during the initial stage of the planning and design of contemporary houses in Malaysia to match privacy requirement and the socio-culture needs to fit the Malaysian users